EVALUATION OF AN INDUCTIVE STRATEGY OF TEACHING MUSIC AND PROGRAMMING TO PRIMARY SCHOOL STUDENTS - Marius Bănuț; Ion Albulescu (Інформаційні технології і засоби навчання)
The traditional teaching strategies have deductive characteristics, while the modern ones have inductive characteristics. But inductive teaching strategies are not always appreciated or recommended in any educational context. Therefore, the present study aimed to design an instructional setting according to the principles of an inductive strategy for teaching content that integrates music with computer programming, and to monitor the effects of teaching, on a long term, on three consecutive generations of fourth-grade students, measuring learning acquisitions through a Learning Achievement Test. In this framework, the students assimilated notions of music notation and formed concepts specific to music education starting from practical exercise, generating sounds electronically using programming languages and the Sonic Pi application, improvising melodies to learn through discovery the variability of sound parameters and reproducing songs from the children's universe, starting from their musical sheets and solving problems of fitting the qualities of sounds into a series of musical notation elements, based on the audio feedback obtained. The analysis of the effects of teaching and the concepts formed in students in the sphere of music education was carried out by measuring the relative state of learning acquisition at the end of the digital instruction based on an inductive teaching strategy, with reference to a fixed criterion: the 25th percentile. Thus, it was found that the percentage of results exceeding the 25th percentile, i.e. 75% of the sample of participants, produced variability at the upper limit of the scoring system. The context of the development of certain transferable computational thinking skills supported learning objectives in the sphere of programming and music composing, and the good results of the students show a concrete performance, and this performance, if considered in proportion to the effort put in, which was a play, a play of music making, i.e. a low effort, can be translated into a good performance and this can be attributed to the inductive teaching strategy.